Multiple-metric hybrid anycast protocol for heterogeneous access networks. (29th July 2011) - Cao, Lijuan; Sharif, Kashif; Dahlberg, Teresa A.; Wang, Yu
The wireless multihop to an Access Point (AP) model appears to be a promising component of future access network architectures. A key challenge is managing diverse resources at APs while discovering efficient multi-hop paths from source to AP based on selection criteria dictated by applications or necessitated by network constraints. We propose a new hybrid proactive/reactive anycast routing protocol that integrates multiple-metrics to calculate path cost and selects the appropriate AP. Simulation analysis shows that our approach outperforms single-metric protocols while supporting flexible service criteria, including load balancing at APs.